Development of a User-Centered "Dini Talk" Alternative Communication System to Support Functional Communication in Children with Cerebral Palsy - Elly Maulina; Cece Rakhmat; Tati Hernawati; Fitri Maulidazani; Salsabila Haliqa; Muthia Syafril; Winda Safarina (Jurnal Pendidikan (Teori dan Praktik), 2026)
Children with cerebral palsy often face communication barriers caused by motor and speech impairments, which limit their participation in classroom activities and daily interaction. Although Augmentative and Alternative Communication (AAC) systems are widely used, many available devices are not sufficiently adapted to users’ motor abilities and educational needs. This study aimed to develop and evaluate DiniTalk, a user-centered AAC system designed to support functional communication in a child with cerebral palsy in an educational setting. The study used a field-based research and development design adapted from the ADDIE model. Data were collected through observation, interviews, and documentation, and were analyzed qualitatively. DiniTalk was designed as a low-cost AAC device with large accessible buttons and auditory output to accommodate motor limitations. The findings showed that the child’s AAC performance improved from 22% in the initial session to 88% in the final session, indicating increased communicative independence and more effective device use. These findings suggest that accessibility-driven AAC design can support functional communication and serve as an instructional aid in special and inclusive education.